Pengembangan Media Promosi Berbasis Website Company Profile Menggunakan CMS Wordpress pada PT Samudra Solusi Agensi Kota Malang - Devita Amalia; Maskur; Ahmad Fauzi (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
PT Samudra Solusi Agensi is a new company engaged in education marketing services. Its reliance on social media and word of mouth has not effectively conveyed complete and professional information. To address the lack of digital platform that enhances visibility and credibility, this study aims to develop a website as promotional media using Figma and WordPress.  This study employed an action research method, with data collected through observation, interviews, questionnaires, and documentation. A total of 30 respondents participated, including 2 marketing experts, 2 IT experts, 1 company director, and 25 clients or prospectives clients. Website quality was assessed using WebQual and effectiveness was evaluated through the EPIC Model.  The results showed that the quality level of the website developed was in the “very good” category with a WebQual score of 90.9%, and the effectiveness level of the website as a promotional media was in the “very effective” category with an EPIC Rate score of 4.5. These results indicated that the developed website successfully met the company’s needs and was suitable for use.  The results indicate that the company profile website developed with WordPress CMS is highly effective as a promotional media. It is expected that PT Samudra Solusi Agensi continuously manage and optimize website content regularly to maintain the relevance of service information.